Protein C Inhibitor Regulates the Thrombin-Thrombomodulin Complex in the Up- and Down Regulation of TAFI Activation - Mosnier, Laurent O.; Elisen, Marc G.L.M.; Bouma, Bonno N.; Meijers, Joost C.M. (Thrombosis and Haemostasis, 2001)
Thrombin Activatable Fibrinolysis Inhibitor (TAFI) is a carboxypeptidase B-like proenzyme that after activation by thrombin down regulates fibrinolysis. Thrombomodulin (TM) stimulates the activation of both TAFI and protein C whereas activated protein C (APC) inhibits the activation of TAFI by down regulating thrombin generation. Recently, protein C inhibitor (PCI) was identified as a potent inhibitor of thrombin bound to TM and it can thereby regulate the balance between TAFI activation, and inhibition of TAFI activation by APC. Both in a purified system and in plasma, activation of TAFI and protein C by IIa-TM could be inhibited by PCI. Previously we found in plasma that at low concentrations (~1 nM), TM predominantly stimulated the activation of TAFI whereas at higher concentrations of TM (~10 nM) the activation of protein C resulted in inhibition of the activation of TAFI. In agreement with this, PCI inhibited the activation of TAFI at 1 nM TM whereas at 10 nM TM PCI inhibited the activation of protein C resulting in an increase in the activation of TAFI. This suggests that PCI can up regulate TAFI activation by inhibiting the protein C activation. PCI may therefore be an important regulator in the balance between coagulation and fibrinolysis by differentially inhibiting the activation of TAFI and of protein C. The local TM concentration plays an important role in the outcome of this process.
Keywords: Fibrinolysis; TAFI; carboxypeptidase U; protein C; protein C inhibitor; thrombomodulin